2022
DOI: 10.1111/jvh.13671
|View full text |Cite
|
Sign up to set email alerts
|

Serum HBV RNA predicts HBeAg clearance and seroconversion in patients with chronic hepatitis B treated with nucleos(t)ide analogues

Abstract: Background: To evaluate the predictive value of serum HBV DNA, HBV RNA, HBcrAg, HBsAg, intrahepatic HBV DNA, and cccDNA for HBeAg clearance and seroconversion during long-term treatment of nucleos(t)ide analogues (NAs) in patients with chronic hepatitis B (CHB).Method: A single center, prospective cohort of CHB patients enrolled between June 2007 and July 2008 was used for this study. Serum HBV RNA levels were retrospectively measured at baseline, 6, 12, 24, 36, 48, 60, 72, and 84 months post-NAs treatment. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
(92 reference statements)
2
12
0
Order By: Relevance
“…In this context, HBcrAg, a composite of 3 distinct proteins—HBeAg, HBcAg, and p22cr—has emerged as a proposed serum marker for disease monitoring and prognosis in CHB. [ 19 , 20 ] In comparison to HBsAg, HBcrAg may represent a superior alternative marker for assessing cccDNA and its transcriptional activity in the liver. The utility of HBcrAg extends beyond disease surveillance, demonstrating promise in predicting treatment response, relapse post-NA discontinuation, as well as disease progression in cirrhosis and the emergence and recurrence of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, HBcrAg, a composite of 3 distinct proteins—HBeAg, HBcAg, and p22cr—has emerged as a proposed serum marker for disease monitoring and prognosis in CHB. [ 19 , 20 ] In comparison to HBsAg, HBcrAg may represent a superior alternative marker for assessing cccDNA and its transcriptional activity in the liver. The utility of HBcrAg extends beyond disease surveillance, demonstrating promise in predicting treatment response, relapse post-NA discontinuation, as well as disease progression in cirrhosis and the emergence and recurrence of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Wang observations align with this, as patients treated with NAs displayed reduced HBV DNA levels, yet liver histology indicated inflammation and fibrosis. [ 6 ] Wang [ 20 ] further found that 63.64% of CHB patients with HBV DNA below the detection threshold still tested positive for serum HBV pgRNA. Our study corroborates these findings, highlighting that virologic rebound in patients with positive HBV pgRNA was 7 times more prevalent than in those with negative HBV pgRNA.…”
Section: Discussionmentioning
confidence: 99%
“…This study has been performed using the database of patients receiving NAs monotherapy, prospectively recruited from Beijing YouAn Hospital, Capital Medical University (Beijing, China) between June 2007 and July 2008 and based on which we have published two previous papers 16,17 . The inclusion criteria were as follows: (a) HBsAg positive >6 months, (b) serum HBV DNA >20,000 IU/mL, (c) aged ≥16 years with ALT >2xULN or aged ≥30 years regardless of ALT levels, (d) HBeAg‐positive, (e) treat‐naïve.…”
Section: Methodsmentioning
confidence: 99%
“…This study has been performed using the database of patients receiving NAs monotherapy, prospectively recruited from Beijing YouAn Hospital, Capital Medical University (Beijing, China) between June 2007 and July 2008 and based on which we have published two previous papers. 16,17 The inclusion criteria were as follows:…”
Section: Patients and Study Designmentioning
confidence: 99%
“…Meanwhile, a certain level of pgRNA which was non- or partially reverse transcribed could also be enveloped and released as HBV RNA virion-like particles[ 9 ]. Some studies have inferred that serum HBV RNA can be a useful marker for monitoring the efficacy of antiviral therapy [ 10 , 11 ], because the level of serum HBV RNA in patients receiving NAs therapy can reflect the presence of the cccDNA and its transcriptional activity in hepatocytes. Moreover, the first-line anti-viral agent such as NAs can reduce the serum HBV DNA down to undetectable level but does not immediately influence the quantification of HBsAg, HBcrAg (hepatitis B core -related antigen), and HBV RNA [ 11 ].…”
Section: Introductionmentioning
confidence: 99%